Health Outcomes of Judo Training as an Organized Physical Activity for Children and Adolescents: A Literature Review - Monika Kowalczyk; Małgorzata Zgorzalewicz-Stachowiak; Maciej Kostrzewa (Children, 2023)
Judo, an organized physical activity for children and adolescents, has gained popularity worldwide. Physical activity is vital during times of rising obesity and a sedentary lifestyle in this age group. The article aims to review the current knowledge of the health benefits of judo-specific exercises for children and youth. Six international scientific databases (PubMed, Scopus, UpToDate, Web of Science, EBSCOhost, and Google Scholar) were searched from 1 January 2007 to 30 September 2022. The search focused on health-related factors regarding healthy preschool and school-aged judo practitioners. Sixteen original studies met the inclusion criteria. School-aged children aged 7–15 years were included in the analysis. The average training time was between two and six hours a week, with the judo intervention mainly ranging from nine months to three years. Most studies registered positive changes caused by judo training. The outcomes focused on maintaining or reducing body fat, increasing bone mineralization, and improving the function of the cardiorespiratory system compared to the non-practicing control group. However, there were no differences between judo and other sports groups. The main conclusions presented health benefits from judo-specific training in school-aged children and may support the World Health Organization recommendations concerning daily physical activity.